Hubungan Obstructive Sleep Apnea dengan Kardiovaskular - Debi Febriani; Faisal Yunus; Budhi Antariksa; Hananto Andrianto (The Indonesian Heart Association, 2011)
Breathing Disorders during sleep seen as potential factors for some Cardio -vascular diseases in last decade. Apnea syndrome during sleep divided into 3 types there are central type, obstruction type and mix type. Obstructive Sleep Apnea (OSA) is the most frequently encountered, marked with apnea episode and hypopnea. There are 4 mechanism relationship of OSA with cardiovascular disease those are mechanical, hemodynamic, neurohor -monal and inflammation. Cardiovascular disease that related to OSA are hypertension, heart failure, acute coronary syndrome, arythmias, stroke, sudden cardiac death. Proper management pro ven improve cardiovascular parameters and increase quality of life.